Баланс основних засобів як інструмент обліку і аналізу: можливості і сфера застосування - Чайка, Тетяна Юріївна; Чуркіна, Ірина Олександрівна (НТУ "ХПІ", 2015)
Обґрунтована доцільність і специфіка застосування балансів основних засобів при проведенні аналізу основних засобів. Уточнено методичні підходи до реалізації принципу збалансованості і пропорційності потреб підприємства в основних засобах; проаналізовано можливості використання балансу основних засобів як інструменту облікової роботи на підприємстві, та допоміжного інструменту при подальшому коефіцієнтному аналізі стану та руху основних засобів підприємства. Уточнено підходи до формування деяких показників, що характеризують ступінь зносу основних засобів і можуть бути розраховані на основі балансів основних засобів. Надано рекомендації щодо включення до балансів основних засобів до загальної системи обліково-аналітичних інструментів на промислових підприємствах.

The article proves the feasibility and the specifics of the application of balances of fixed assets the analysis of fixed assets; specified tasks that can be solved with their help. Improved methodical approaches to the implementation of the principle of balance and proportion of fixed assets; analyzed the possibility of using the balance of fixed assets as a tool of accounting work at the enterprise and aid in the further coefficient analysis of the status and movements of fixed assets of the company. Refined approaches to the formation of some indices characterizing the degree of wear of fixed assets, which can be calculated based on balances of fixed assets. Recommendations for inclusion of balances of fixed assets in the common system of accounting and analytical tools in industrial enterprises. This study shows that the balance method is a very effective tool, which allows for the application of the principle of proportionality and balance the needs of businesses in fixed assets. Using balance method seems appropriate at all levels of planning-strategic, tactical and operational. Equity method appropriate to apply comprehensively for the further ratio analysis, as well as an aid in verifying the initial data and accuracy of analytical calculations of various factors on the resulting figure.
The Balance of fixed assets as a tool of accounting and analysis: opportunities and scope
Keywords: балансовий метод; балансова модель; коэффициентный анализ; матеріально-технічне забезпечення; фінансово-господарська діяльність; balance method; balance model; ratio analysis